The effect of X-linked dosage compensation on complex trait variation - Julia Sidorenko (Nature Portfolio, 2019)
Dosage compensation (DC) on the X chromosome has predictable effects on genetic and phenotypic trait variance. Here, the authors use information for 20 quantitative traits in the UK Biobank and across-tissue gene expression to compare X-linked heritability and the effects of trait-associated SNPs between the sexes.